Increased burned area in the Pantanal over the past two decades - Correa, Danielle Blazys [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Wildfires are behaving differently now if compared to other time in history in relation to frequency, intensity and affected ecosystems. In Brazil, unprecedent fires are being experienced in the last 10 years and to prevent and minimize similar disasters we must understand more about the natural and human influences on fires on each ecosystem as well as the gaps to fire combat strategies. The Brazilian Pantanal is the largest contiguous wetland in the world and a complex environmental system. In 2020 Pantanal experienced a catastrophic wildfire which burned out of control that shocked the world. The fire in Pantanal is expected to escalate given the increase in drought episodes, inadequate fire management strategies and weak environment regulations. In this study, we analyzed recent patterns and changes in fire frequency across the Pantanal based on land use and cover classes. The inter-annual variability of the fire and land cover changes between 2000 and 2021 was assessed using burned area (BA) from MCD64A1 V.6 product and land use and land cover (LULC) data from Landsat imagery. Our results showed that while smaller BA were more frequent for all LULC, forest and grassland classes represented much larger BA with lower frequencies. Cropland showed the smallest burned area among the LULC. Given the differences in the rates of recovery and regeneration after fire for different classes, Pantanal should be systematically monitored to develop a more effective fire combat strategy. We understand that our work demonstrates fundamental spatiotemporal clues to managers to strategically approach unusual fires with result of what periods were exceptional burned according to LULC classes, as observed for Forests in 2020 and an exponential burning growth in cropland during late dry (LD) season since 2014.

Incêndios florestais têm se comportado de forma diferente nos anos mais recentes se comparados a outros períodos da história em relação à frequência, intensidade e ecossistemas afetados. No Brasil, queimadas sem precedentes têm sido identificadas nos últimos dez anos e para prevenir e minimizar desastres similares é necessário compreendermos mais sobre as influências naturais e antrópicas nas queimadas de cada ecossistema, bem como as lacunas que prejudicam estratégias de combate ao fogo. O Pantanal Brasileiro é a maior área úmida contínua do mundo e um complexo sistema ambiental. Em 2020 o Pantanal sofreu uma queimada catastrófica que impressionou o mundo. É esperado que o fogo no Pantanal ganhe escala devido ao aumento de episódios de seca, estratégias de combate ao fogo inadequadas e fracas regulações ambientais. Nesse estudo, foram analisados padrões e mudanças recentes na frequência de queimadas no Pantanal baseado em classes de uso e cobertura do solo. A variabilidade interanual de queimadas e mudanças na cobertura de solo entre 2000 e 2001 foram avaliadas usando a área queimada do produto MCD64A1 V.6 e uso e cobertura do solo extraídas a partir de imagens Landsat. Nossos resultados mostram que enquanto pequenas áreas queimadas foram mais frequentes em todas as classes de uso e cobertura de solo, as classes de floresta e gramíneas apresentam áreas queimadas mais extensas, ainda que pouco frequentes. A classe de agricultura apresentou as menores áreas dentre as demais classes. Devido a diferença nas taxas de recuperação e regeneração após a passagem do fogo nas diferentes classes, o Pantanal deve ser sistematicamente monitorado para que sejam desenvolvidas estratégias de combate ao fogo eficientes. Nós entendemos que este trabalho demonstra dicas espaço-temporais fundamentais para gestores para que o combate de queimadas atípicas, com resultados dos períodos que foram excepcionalmente queimados por classe de uso e cobertura de solo, como observado para Florestas em 2020 e o exponencial aumento de queimadas em áreas agrícolas na estação seca desde 2014.
Aumento da área queimada no Pantanal ao longo das últimas duas décadas
Keywords: Land use and land cover changes; Burned areas; Tropical wetland; Extreme events